Biochemical Characterization of the Induced Immune System of Pistachio (Pistacia vera) by Salicylic Acid. Issue 2 (2nd April 2020) - Ghamari, Mahboob; Hosseininaveh, Vahid; Talebi, Khalil; Nozari, Jamasb; Allahyari, Hossein
ABSTRACT: Despite the economic importance of pistachio very little studies have been performed on its defense physiology. Due to lack of effective method among pest management programs, pesticides, despite their known some adverse features, is the only and last option for control of pests in pistachio orchards in most cases. The present study has been conducted to determine total phenolic, total protein content, antioxidant defense response and phenylalanine ammonia-lyase activity in the leaves of pistachio seedling induced by salicylic acid (SA). Results showed that the concentrations 1 and 4 mM of SA increased the phenolic content and PAL activity. The enhanced PAL activity led to the improvement of the quantity of phenolic compounds. In addition, the SA application showed an enhancing impact on total protein content and oxidative enzymes (catalase, guaiacol peroxidase, ascorbate peroxidase, and polyphenol oxidase) activity. In all experiments the SA elicitation effect was concentration- and time-dependent. Repeated measurement statistical analysis revealed that the maximum elicitation effect of SA occurred in 3 to 9 days after the treatment. SA effects on plant defensive systems are highly complicated, and further investigations are needed to clarify the underlying mechanisms. These results can be used in designing of integrated pest management programs of pistachio pests focusing on applying safe and environment-friendly controlling methods.